Frequency of Neuropathy Symptoms in Diabetic Patients - Gnanamoorthy, Tharani; Paul, Jibi; Alagesan, Jagatheesan; Narayanaswamy, Harikrishnan (Scripta Medica, 2024)
Background/Aim: One of the most common consequences of diabetes mellitus is diabetic neuropathy, which is triggered on by nerve damage. The characteristic of neuropathies is a progressive loss of nerve fibre function resulting in numbness, tingling, aching, burning and throbbing sensations. In addition, it adds to the risk of falls, joint deformities, muscular atrophy and foot ulcers. The study aimed to analyse the incidence of motor and sensory dysfunctions in patients with diabetes mellitus in Chennai, India.Methods: This was an observational study of analytic type. Clinically diagnosed diabetic patients between the age of 45 to 60 years were considered for this study. Patients who consented to participate in this study, with a history of diabetes mellitus spanning more than ten years were chosen. Patients found to have other causes of neuropathy, diabetic ulceration, lactating (or) pregnant women and non-cooperative patients were excluded from this study. All the subjects enrolled in the study at the aforementioned centres were given the Michigan neuropathy screening instrument (MNSI). Total score of MNSI was calculated and interpreted for the prevalence. Results: A total of 246 subjects have participated in this study out of which 54 % were male and 46 % were female, 127 (51 %) had diabetic peripheral neuropathy, 41 (17 %) had partial diabetic neuropathy and 78 (32 %) had no symptoms of diabetic neuropathy. Conclusion: Through the questionnaire and physical examination, the current study demonstrated a high prevalence of motor and sensory impairments as well as diabetic neuropathy symptoms in the diabetic population.
Keywords: Diabetes mellitus; Diabetic neuropathies; Michigan neuropathy screening instrument (MNSI); Peripheral nerve injury